Uji Aktivitas Antibakteri Gel Kombinasi Ekstrak Etanol Daun Sintrong (crassocephalum crepidioides (Benth.) S.Moore) Dan Bawang Daun (Allium fistulosum L.) - Apriana Ulan Dari MS; Hindri Syahputri; Haris Munandar Nasution; Zulmai Rani (Journal of Pharmaceutical and Sciences, 2026)
Skin diseases are the most common type of skin disease in tropical countries like Indonesia. One of the main causes is bacterial infection. Sintrong leaves (Crassocephalum crepidioides (Benth.) S. Moore) and scallion (Allium fistulosum L.) contain secondary metabolites with antibacterial potential. The objective of the research was to determine the antibacterial activity of sintrong leaf extracts (Crassocephalum crepidioides (Benth.) S. Moore) and scallion (Allium fistulosum L.) formulated in gel form. This research was experimental in nature with the preparation of gel preparations using variations in the ratio of sintrong leaf extract (Crassocephalum crepidioides (Benth.) S.Moore) and spring onion (Allium fistulosum L.) (2:3, 2:2, 3:2). Evaluation parameters included organoleptic tests, homogeneity, pH, viscosity, spreadability, and adhesiveness. Antibacterial activity was tested by the disc diffusion method on Staphylococcus aureus and Staphylococcus epidermidis using clindamycin as a positive control and gel base as a negative control. The results showed that all formulas met the physical criteria of gel preparations with a pH of 5.1–5.8, viscosity of 23726–38580 cPs, spreadability in the range of 5–7 cm, and adhesiveness of >4 seconds. Antibacterial activity showed a zone of inhibition in all formulas, with the largest diameter in formula F3 (3:2), with an average inhibition diameter of 18.23 ± 0.67 mm on Staphylococcus aureus and 17.51± 0.30 mm on Staphylococcus epidermidis, which is categorized as strong.